Gestión comercial de la empresa panadería y pastelería La Favorita del cantón Babahoyo provincia de Los Ríos, del periodo 2023. - Vega Carbo, Micheld Adriana (2025)
The case study "Commercial Management of La Favorita Bakery and Pastry Shop" analyzes the main challenges faced by this company in Babahoyo during the year 2023. Founded in 2012, La Favorita has stood out for its local expansion, but currently faces problems related to fluctuating demand, insufficient staff training, and a poorly defined brand identity. These factors have caused variations in product quality, operating cost overruns, and difficulties in competing against larger and more differentiated chains. In addition, the limited presence on social media and the lack of effective promotions have reduced its market positioning. The study seeks to diagnose these problems through surveys and direct observations, addressing aspects such as the perception of quality, customer service, prices, and variety of products. Among the findings, the need to standardize production processes, diversify the offer, strengthen digital advertising, and develop loyalty strategies stands out. This research is part of the Financial, Administrative and Marketing Management line, with the aim of optimizing the commercial management of La Favorita, increasing its competitiveness and ensuring its sustainability in the local market.